PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA UPIK FUTSAL BANJARMASIN - Teguh Wicaksono (Islamic University of Kalimantan MAB Banjarmasin, 2017)
Focusing on customer satisfaction is one of the keys to the success of a business, so the company can gain profit and wider market share. Service quality dimensions are: physical evidence, reliability, responsiveness, assurance and empathy are used by companies to better understand expectations or customer perceptions of the desired service, resulting in improved service quality. This research is an associative survey research using nonprobability sampling technique, using multiple regression analysis technique. The result of hypothesis testing proves that all independent variables consisting of physical evidence, reliability, responsiveness, assurance and empathy partially have a positive and significant effect on the dependent variable that is customer satisfaction. The influence of each independent variable in sequence that is, reliability variable equal to 0,919, variable of empathy equal to 0,913, variable of responsiveness equal to 0,811, variable of guarantee equal to 0,805 and physical evidence variable equal to 0,789. Salain is also variable physical evidence, reliability, responsiveness, assurance and empathy simultaneously have a positive and significant effect on customer satisfaction with the magnitude of influence is 0.956. Keywords: Service Quality Dimension, Customer Satisfaction